Freezing Technology: Challenges and Prospects for Sustainable Development in Urban Infrastructure - Shunji Kanie (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
Ground freezing has been broadly applied to construction and maintenance works of infrastructures because of its environmental friendliness. Since freezing technology represented by ground freezing can improve the strength of soil as well as its water-tightness, it becomes an essential technology for construction and maintenance of urban infrastructures where the use of space in underground has already been highly integrated. In this paper, overview of the freezing technology is introduced with some important characteristics of freezing soil for practical application. In addition, freezing technology is used for interesting works which could not be completed without freezing, and the state of the arts in freezing technology is presented. A pipe-in-pipe, now the authors are developing, is an example to utilize the potential of frozen sand, and the effect of freezing is explained with experimental results.